Application of theoretical model of marketing productivity to evaluate performance of vegetable and fruit wholesalers in Selangor, Malaysia - Syed Yusof, Sharifah Shahidah (2019)
The vegetables and fruits industry has been and will continue to be a key economic activity in Selangor in the coming decades. However, the vegetables and fruits industry in Selangor seems to have obstacles in competing in an open economic trade, which is mostly dominated by large economic sectors. The fruits and vegetables sector continues to face inefficiencies arising from structural defects, such as poor marketing structures, labour shortage and increasing cost of inputs. At the same time, the price of fruits and vegetables will continue to be exposed to swings and shifts in demand. Hence, productivity and profitability from wholesalers continue to lag. The lack of resources that leads to the inability to measure the productivity of fruits and vegetables is the main problem faced by this industry. Hence, this study explores this problem using the Theoretical Model of Marketing Productivity (TMMP) as a base for carrying out measurements of productivity through the identification of possible determinant variables in this industry. This study aims to answer the following problems; firstly, regarding the issues faced by the fruits and vegetables market in Selangor; secondly, the current profiles of fruits and vegetables wholesalers in Selangor and lastly, to know which factor affects marketing productivity of the fruits and vegetables industry in Selangor. Data collection was conducted at major wholesalers in the Selangor area. A total of 374 valid questionnaires were collected from the survey by using convenience sampling technique. ‘Statistical Package Social Sciences’ (SPSS) was applied in the data analysis using multiple regression and Pearson’s Correlation analyses to test the hypotheses developed. The findings of this study largely support the hypothesized relationships proposed in the theoretical model. Specifically, the results revealed that all marketing resources, financial performance and price gave a positive effect on marketing productivity. Hence, the model proposed in this study has enhanced the understanding and evaluation of the vegetables and fruits Small and Medium Enterprise’s (SME’s) performance. The implication for the industry’s management is to control these significant factors that affect its industrial performance which can be used as policy tools in decision-making by government agencies. The study also benefits practitioners, especially at the industrial management level, and government agencies in understanding the factors which can improve the industry’s marketing productivity. In conclusion, this study suggests research directions to advance the theorization and empirical testing of TMMP in the future.